PERFORMANCE ANALYSIS WITH SHARPE INDEX APPROACH IN FIXED INCOME ISLAMIC MUTUAL FUNDS - Yulis Nurul Aini; Baroroh Lestari; Yekie Senja Oktora (CURRENT ADVANCED RESEARCH ON SHARIA FINANCE AND ECONOMIC WORLDWIDE, 2022)
The purpose of this study is to gain an understanding of how the performance of fixed income sharia mutual funds has fared in the Indonesian Capital Market. The information used in the research came from financial reports and publications that were made available on the Indonesia Stock Exchange. These reports covered the time period 2018-2020. For the purpose of providing an explanation of the performance of fixed income Sharia mutual funds, the financial statement is studied using Index Sharpe. According to the findings of this research, the performance of fixed income sharia mutual funds has a negative performance during the period of 2018-2020.